Long Non-coding RNA HOTAIR Promotes Parkinson’s Disease Induced by MPTP Through up-regulating the Expression of LRRK2 - Liu, Sen; Cui, Bei; Dai, Zhen-xia; Shi, Peng-ke; Wang, Zhao-hui; Guo, Yuan-yuan (Current Neurovascular Research, 2016)
Homeobox (HOX) transcript antisense RNA (HOTAIR), as a long intergenic noncoding RNA (lincRNA), is known to be overexpressed in several cancers. However, the role of HOTAIR in Parkinson’s disease (PD) remains unclear. A mouse model of PD was developed by intraperitoneal injection of MPTP (N-methyl-4-phenyl-1,2,3,6- tetrahydropyridine). The expression of HOTAIR and LRRK2 (leucine-rich repeat kinase 2) were detected in the PD mice and in Human neuroblastoma cell lines SH-SY5Y pretreated with MPP+ (N-methyl-4-phenylpyridinium). The effect of HOTAIR on the expression of LRRK2 was examined in SH-SY5Y cells through overexpressing HOTAIR. A MTT (3- (4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide) assay was performed to measure the cell viability of SH-SY5Y cells. si-HOTAIR (siRNA-HOTAIR) was utilized to investigate the effect of HOTAIR on the expression of LRRK2 in vivo. In this study, upregulation of HOTAIR and LRRK2 were found in the midbrain of PD mice induced by MPTP and in SH-SY5Y cells pretreated with MPP+. With the presence of HOTAIR overexpression in SH-SY5Y cells, the expression of LRRK2 was increased compared with that in the control. HOTAIR knockdown showed a protective effect on the cell viability of SH-SY5Y cells pretreated with MPP+, which was abrogated by overexpression of LRRK2. In mouse model of PD treated with si-HOTAIR, the expression of LRRK2 was decreased. In conclusion, high expression of HOTAIR promoted the onset of PD induced by MPTP. Moreover, the finding that HOTAIR promoted PD induced by MPTP through regulating LRRK2 expression could add our understanding of the molecular mechanisms in PD.
Keywords: Homeobox (HOX) transcript antisense RNA